Observations of the copulatory behaviour of the Ocean pout (Macrozoarces americanus) - Mercer, Sandra; Brown, Grant E.; Clearwater, Susan; Yao, Zuxo (Ottawa Field-Naturalists' Club, 1993)
The Ocean Pout (Macrozoarces americanus) is a common species of eelpout found off the coast of Newfoundland. It has previously been suggested that the Ocean Pout is an internally fertilizing species but no direct observations of this have been reported. What is though to be the first observation of the copulatory behaviour of mature Ocean pout in the wild is described here. Similar behaviour was videotaped under laboratory conditions